Preparation method of modified Ti3C2TxMXene reinforced polymethyl methacrylate composite material
Through KH-570 surface modification and ultrasonic layering treatment, the modified Ti3C2Tx MXene and methyl methacrylate composite material are uniformly dispersed in the hydrophobic polymer, solving the dispersion and interface stability of MXene in the hydrophobic polymer. , significantly improves the mechanical properties and fracture toughness of composite materials.
Patent Information
- Application Number
- CN202411430454.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
MXene is difficult to disperse in hydrophobic polymers, resulting in interface instability and limited performance improvement, and prone to agglomeration, affecting the mechanical properties of the composite materials.
Through KH-570 surface modification and ultrasonic layering treatment, the modified Ti3C2Tx MXene was uniformly dispersed with methyl methacrylate (MMA), and azobisisobutyronitrile was added during the polymerization process to enhance interface binding and load transfer efficiency. .
The fracture toughness and tensile properties of the composite material are significantly improved, the interface combination between Ti3C2Tx and PMMA matrix is enhanced, the mechanical properties and dispersion of the material are improved, and crack deflection and energy loss are caused during damage.
Smart Images

Figure CN119264311A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and more specifically, relates to a modified Ti3C2T x Preparation method of MXene reinforced polymethyl methacrylate composites. Background Art
[0002] Compared with single polymer materials, polymer-based composite materials have better application prospects due to the high performance brought by the composite effect, interface effect and scale effect between their multiphase structures. Two-dimensional graphene-like nano-layered MXene has unique two-dimensional layered structure, large specific surface area, high elastic modulus, excellent mechanical properties and rich surface functional groups, and is considered to be an excellent reinforcement material for polymer matrix. At the same time, MXene's excellent metal-level conductivity and other advantages are also considered to be very suitable for application in functional fields such as electromagnetic shielding. The key is to use polymers to encapsulate MXene or MXene / functional particle composites with a certain overlap structure, which can effectively avoid MXene oxidation while ensuring the rationality and integrity of the structure, so that the impedance matching is reasonable and efficient shielding performance can be achieved. Therefore, MXene-enhanced polymer-based composites are an effective way to design, develop and manufacture advanced structural and functional integrated materials.
[0003] However, the current mature mass production method of MXene is carried out in an aqueous environment, resulting in the surface active functional groups being mostly hydrophilic functional groups, which are difficult to wet with hydrophobic polymers and cannot be directly dispersed in hydrophobic polymers. After MXene is dehydrated and then dispersed in a hydrophobic polymer matrix, MXene flakes tend to agglomerate, which not only makes it difficult to form a strong interface, but also is not conducive to the transfer of loads between the matrix and the reinforcement, so that MXene as a reinforcement can only improve the performance of composite materials to a limited extent. Summary of the invention
[0004] The purpose of the present invention is to provide a modified Ti3C2T x Preparation method of MXene reinforced polymethyl methacrylate composite material to solve the problem of reinforced Ti3C2T x The poor wettability of MXene with methyl methacrylate (MMA) improves Ti3C2T x Dispersion of MXene in MMA; Solving the problem of reinforcement Ti3C2T x The problem of uniform dispersion in the polymethyl methacrylate (PMMA) matrix while maintaining structural integrity and avoiding agglomeration, and strengthening the reinforcement Ti3C2T x The interface between the PMMA matrix and the reinforcement Ti3C2T xThe transfer efficiency between the PMMA matrix and the composite material is improved, and the mechanical properties of the composite material are improved; the reinforcement Ti3C2T x The pull-out of the sheets and the resulting crack deflection strengthen the PMMA-based composite material and significantly improve the fracture toughness of the composite material.
[0005] To achieve the above object, the present invention is implemented by the following technical solutions:
[0006] The present invention provides a modified Ti3C2T x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, comprising:
[0007] Ti3C2T x After acid corrosion, the ceramic powder was cleaned and centrifuged to obtain Ti3C2T x The mixture was precipitated by centrifugation;
[0008] Dissolving KH-570 in an ethanol aqueous solution to prepare a KH-570 solution;
[0009] The Ti3C2T x The centrifugal precipitation mixture was added to the KH-570 solution, stirred evenly, and then subjected to ultrasonic layering treatment to achieve the Ti3C2T x Surface modification and delamination;
[0010] For surface modified Ti3C2T x After the solution was centrifuged, the upper layer of the solution was vacuum filtered to obtain surface-modified single-layer and few-layer Ti3C2T x ;
[0011] The surface modified single layer and few layer Ti3C2T x Add it into methyl methacrylate, stir it evenly and then perform ultrasonic layering treatment to obtain surface modified Ti3C2T x Methyl methacrylate dispersion;
[0012] Surface modified Ti3C2T x Azobisisobutyronitrile is added to the methyl methacrylate dispersion, the mixture is evenly mixed and then bulk polymerization is carried out to obtain the product.
[0013] Preferably, the Ti3C2T x The method for preparing ceramic powder includes:
[0014] Ti, Al and C powders are sintered to form a Ti3AlC2 ceramic bulk material, and the prepared ceramic bulk material is ground to obtain Ti3AlC2 ceramic powder; wherein the molar ratio of Ti, Al and C powders is (2.9~3.2):(1~1.4):(1.8~2.2); the preferred ratio is 3:1.2:2.
[0015] Further preferably, the Ti, Al and C powders are mixed in proportion, sintered without pressure at 1300-1400° C., and then ground into Ti3AlC2 ceramic powder with a fineness of 100-1200 mesh.
[0016] Preferably, the acid corrosion comprises:
[0017] The Ti3AlC2 ceramic powder is placed in a mixed solution of hydrochloric acid and lithium fluoride or an aqueous solution of hydrofluoric acid, and fully stirred at 20-70° C. to obtain a mixed suspension after corrosion.
[0018] Further preferably, the concentration of the hydrochloric acid is 9-12 mol / mL, the volume mass ratio of hydrochloric acid to lithium fluoride is (5-25) mL: (0.2-2) g; the concentration of hydrofluoric acid in the aqueous solution of hydrofluoric acid is 10-70 wt.%. Ti3AlC2 ceramic powder is added to the above acid solution, mixed, and then a magnetic rotor is added and stirred in an oil bath environment of 20-70°C for 12-96 hours.
[0019] Further preferably, the mixed suspension after corrosion is washed with 5 to 100 mL of deionized water and centrifuged, and the supernatant is discarded, and the process is repeated for several times until the pH value of the supernatant is greater than or equal to 6; the mixture is washed with 5 to 100 mL of deionized water and centrifuged, and the supernatant is discarded, and the process is repeated for 3 to 20 times to obtain the Ti3C2T4O3O ... x The mixture was pelleted by centrifugation.
[0020] Preferably, the preparation method of the KH-570 solution comprises:
[0021] KH-570 is added to an ethanol aqueous solution, wherein the mass ratio of KH-570 to the ethanol aqueous solution is 1:(10-100), the mass ratio of ethanol to deionized water in the ethanol aqueous solution is (8-10):(2-0), and the preferred ratio is 9:1, acetic acid is added to adjust the pH value of the solution to 4-6, and magnetic stirring is performed for 2-4 hours to completely hydrolyze KH-570 to obtain the product.
[0022] Preferably, the Ti3C2T x The mass ratio of the centrifugal precipitation mixture to KH-570 is 1:(0.5~1).
[0023] Preferably, the ultrasonic delamination process comprises:
[0024] The ultrasonic layering treatment was carried out under the protection of argon atmosphere for 1 to 4 hours, and the temperature was kept below 35°C during the ultrasonic process.
[0025] Preferably, the surface-modified Ti3C2T x The solution centrifugation conditions include: low-speed centrifugation at 2000-4000 rpm for 2-8 min; further, the Ti3AlC2 that was not completely etched and the unreacted Ti3C2T x The upper solution is the surface-modified single-layer and few-layer Ti3C2T x Colloidal solution; surface modified single layer and few layer Ti3C2T x The colloidal solution was vacuum filtered to remove the unreacted KH-570 and obtain surface-modified single-layer and few-layer Ti3C2T x .
[0026] Preferably, the modified Ti3C2T x Ti3C2T in MXene-reinforced polymethyl methacrylate composites x The content of Mxene is 0.001wt.% ~ 20wt.%.
[0027] Preferably, the azobisisobutyronitrile and the surface-modified Ti3C2T x The mass ratio of methyl methacrylate dispersion is (0.4~0.8):100.
[0028] Preferably, the bulk polymerization comprises:
[0029] Prepolymerize in a water bath at 60-70°C for 0.5-1h to obtain a prepolymer solution;
[0030] The obtained prepolymer solution was transferred to a sealed container and polymerized in a water bath at 70-90°C for 12-24 hours, and then polymerized in a water bath at 90-95°C for 1-2 hours.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The modified Ti3C2T provided by the present invention x The preparation method of MXene reinforced polymethyl methacrylate composite material has simple process and low cost, and solves the problem of reinforcing body Ti3C2T x The encapsulation problem in polymers solves the problem of reinforcing Ti3C2T x The dispersion problem in the polymer matrix PMMA and the reinforcement Ti3C2T x The interface between the PMMA matrix and the reinforcement Ti3C2T x The transfer efficiency between Ti3C2T and PMMA matrix isx It can cause crack deflection and increase energy loss by ply pullout, thus significantly improving the fracture toughness of the composite material. The tensile properties and fracture toughness of the composite material obtained were improved by 25.37% and 87.03% respectively;
[0033] The present invention maintains Ti3C2T x Under the premise that the MXene structure is intact, Ti3C2T x Evenly dispersed into PMMA matrix, Ti3C2T x Encapsulation preservation;
[0034] The method of the present invention is easy to control and can accurately quantify single-layer and few-layer Ti3C2T x Different Ti3C2T x Addition ratio of composite materials;
[0035] The PMMA-based composite material prepared by the method of the present invention has high interface bonding strength, effectively improves the load transfer efficiency between the matrix and the reinforcement, and has excellent mechanical properties. x It can cause crack deflection and increase energy loss through ply pullout, which significantly improves the fracture toughness of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Surface modification of KH-570 with Ti3C2T x Schematic diagram of the reaction process of surface functional groups;
[0037] Figure 2 The surface modification of KH-570 before and after modification of Ti3C2T in the preparation process of Example 1 of the present invention x Photos of the dispersion in MMA;
[0038] Figure 3 Ti3C2T after surface modification of KH-570 in the preparation process of Example 1 of the present invention x High-resolution XPS elemental spectra of C 1s, Ti 2p, O 1s and Si 2p;
[0039] Figure 4 In the process of preparing Ti3C2T in the present invention, x , KH-570 and Ti3C2T after surface modification of KH-570 x FTIR spectrum of
[0040] Figure 5 KH-570 surface-modified Ti3C2T prepared in Example 1 of the present invention xPhotos of MXene-reinforced PMMA composite samples; (a) is sample 1, (b) is sample 2;
[0041] Figure 6 (a) and (c) are Ti3C2T prepared by the method of Example 3. x CT three-dimensional reconstruction images of composite materials with mass fractions of 0.2% and 1%, (b) and (d) are the distribution of MXene in the matrix drawn according to the test results of (a) and (c);
[0042] Figure 7 Ti3C2T prepared by the method of Example 3 x Comparison of mechanical properties of composite materials with mass fractions of 0%, 0.1%, 0.2%, 0.5% and 1%;
[0043] Figure 8 Ti3C2T prepared by the method of Example 3 x Comparison of the fracture toughness and critical energy release rate values of composite materials with mass fractions of 0%, 0.1%, 0.2%, 0.5% and 1%, respectively. DETAILED DESCRIPTION
[0044] The preferred embodiments of the present invention will be described in more detail below in conjunction with the accompanying drawings and specific examples.
[0045] Example 1
[0046] This embodiment provides a method of using KH-570 to modify the surface of Ti3C2T x The preparation method of MXene reinforced PMMA composite material comprises the following steps:
[0047] S1: Ti3C2T x Preparation
[0048] S1.1: After mixing Ti, Al and C powders in a molar ratio of 3:1.2:2, a high-purity ternary layered Ti3AlC2 ceramic bulk material is prepared by a pressureless sintering process at 1350°C, and the prepared Ti3AlC2 ceramic bulk material is drilled by a drilling machine to obtain Ti3AlC2 ceramic powder; the prepared Ti3AlC2 ceramic powder is sieved through a 325-mesh sieve;
[0049] S1.2: Add 1 g of the prepared Ti3AlC2 ceramic powder to a mixed solution of 10 mL of 12 mol / mL hydrochloric acid and 1.0 g of lithium fluoride, add a magnetic rotor and stir in an oil bath at 35°C for 24 h to remove the Al atomic layer in Ti3AlC2;
[0050] S1.3: Wash the corroded mixture suspension with 50 mL of deionized water and centrifuge, discard the supernatant, and repeat several times until the pH value of the supernatant is greater than or equal to 6;
[0051] S1.4: After the pH value of the supernatant is greater than or equal to 6, continue to wash with 40 mL of deionized water and centrifuge, pour off the supernatant, repeat 3 to 5 times to obtain the final cleaned Ti3C2T x The mixture was pelleted by centrifugation.
[0052] S2: KH-570 vs Ti3C2T x Surface modification and multilayer Ti3C2T x Ultrasound stratification
[0053] S2.1: Add 0.1 g KH-570 to 10 g ethanol-water solution (the mass ratio of ethanol to deionized water is 9 g:1 g), add acetic acid to adjust the pH value of the solution to 5, and stir magnetically for 4 h to completely hydrolyze KH-570;
[0054] S2.2: The cleaned Ti3C2T x The mixture was centrifuged and precipitated, and then added to the hydrolyzed KH-570 solution. x The mass ratio of the mixture to KH-570 was 1 g:1 g. After being stirred evenly, the mixture was subjected to ultrasonic layering treatment for 2 h under the protection of argon atmosphere. The temperature was kept below 35 °C during the ultrasonic process. x While peeling off into single layer and few layers, Ti3C2T x The hydroxyl groups on the surface react with the silanol groups produced by the hydrolysis of KH-570 to form chemical bonds, thus achieving the goal of bonding Ti3C2T x Surface modification and delamination.
[0055] Figure 1 For the process of KH-570 surface modification Ti3C2T x Schematic diagram of the reaction process of surface functional groups.
[0056] Figure 2 Ti3C2T before and after surface modification of KH-570 x The dispersion of Ti3C2T in MMA. As can be seen from the figure, after the same centrifugation time, the surface modified Ti3C2T x Ti3C2T without KH-570 surface modification can still be uniformly dispersed in non-polar MMA. x Then they gather together and sink to the bottom.
[0057] Figure 3 Ti3C2T after surface modification of KH-570 xThe high-resolution XPS elemental spectra of C 1s, Ti 2p, O 1s and Si 2p of Ti3C2T x There is Si element bonding on the surface, combined with Figure 1 Schematic diagram of the reaction process, which shows that KH-570 successfully modified Ti3C2T x .
[0058] Figure 4 Ti3C2T x , KH-570 and Ti3C2T after surface modification of KH-570 x FTIR spectrum of -1 The new absorption peak at is attributed to the Si-O-Ti-C covalent bond, indicating that KH-570 can achieve the effect of bonding Ti3C2T x surface modification.
[0059] S3: Preparation of Ti3C2T x Mxene reinforced PMMA composites
[0060] S3.1: Surface modified and delaminated Ti3C2T x The solution was centrifuged at 4000 rpm for 3 min to remove the Ti3AlC2 that was not completely etched and the unreacted Ti3C2T x The upper solution contains surface-modified single-layer and few-layer Ti3C2T x colloidal solution; single-layer and few-layer Ti3C2T x The colloidal solution was vacuum filtered to remove the unreacted KH-570 and obtain surface-modified single-layer and few-layer Ti3C2T x ;
[0061] S3.2: The single layer and few layers of Ti3C2T obtained after the above surface modification x After adding to MMA and stirring evenly, ultrasonic layering was performed for 2 h under argon atmosphere protection. The temperature was kept below 35 °C during the ultrasonic process to obtain Ti3C2T x The uniformly dispersed MMA solution was used to determine the Ti3C2T x concentration;
[0062] S3.3: Preparation of modified Ti3C2T xAzobisisobutyronitrile (AIBN) was added to the mixed solution of MMA with a mass fraction of 0.1%, and the mass ratio of AIBN to MMA mixed solution was 0.5 g:100 g. After mixing evenly, bulk polymerization was carried out, and prepolymerization was carried out in a water bath at 70 ° C for 0.5 h to obtain a prepolymer solution. The obtained prepolymer solution was transferred to a sealed container, polymerized in a water bath at 70 ° C for 12 h, and then polymerized in a water bath at 90 ° C for 1 h. After cooling, KH-570 surface-modified Ti3C2T x MXene reinforced PMMA composites.
[0063] Example 2
[0064] This embodiment provides a method of using KH-570 to surface modify Ti3C2T x The preparation method of MXene reinforced PMMA composite material comprises the following steps:
[0065] S1: Ti3C2T x Preparation
[0066] S1.1: After mixing Ti, Al and C powders in a molar ratio of 3:1.3:2, a high-purity ternary layered Ti3AlC2 ceramic block material is prepared by a pressureless sintering process at 1300°C, and the prepared Ti3AlC2 ceramic material is drilled by a drilling machine to obtain Ti3AlC2 ceramic powder; the prepared Ti3AlC2 ceramic powder is sieved through a 325-mesh sieve;
[0067] S1.2: Add 1 g of the prepared Ti3AlC2 ceramic powder to a mixed solution of 20 mL of 9 mol / mL hydrochloric acid and 1.8 g of lithium fluoride, add a magnetic rotor and stir in an oil bath at 38°C for 30 h to remove the Al atomic layer in Ti3AlC2;
[0068] S1.3: Wash the corroded mixture suspension with 50 mL of deionized water and centrifuge, discard the supernatant, and repeat several times until the pH value of the supernatant is greater than or equal to 6;
[0069] S1.4: After the pH value of the supernatant is greater than or equal to 6, continue to wash with 40 mL of deionized water and centrifuge, pour off the supernatant, repeat 5 to 10 times to obtain the final cleaned Ti3C2T x The mixture was pelleted by centrifugation.
[0070] S2: KH-570 vs Ti3C2T x Surface modification and multilayer Ti3C2T x Ultrasound stratification
[0071] S2.1: Add 0.1 g KH-570 to 5 g ethanol aqueous solution (the mass ratio of ethanol to deionized water is 8 g:2 g), add acetic acid to adjust the pH value of the solution to 5, and stir magnetically for 3.5 h to completely hydrolyze KH-570;
[0072] S2.2: The cleaned Ti3C2T x The mixture was centrifuged and precipitated, and then added to the hydrolyzed KH-570 solution. x The mass ratio of the mixture to KH-570 was 1 g:0.75 g. After being stirred evenly, the mixture was subjected to ultrasonic layering treatment for 3 h under the protection of argon atmosphere. The temperature was kept below 35 °C during the ultrasonic process. x While peeling off into single layer and few layers, Ti3C2T x The hydroxyl groups on the surface react with the silanol groups produced by the hydrolysis of KH-570 to form chemical bonds, thus achieving the goal of bonding Ti3C2T x Surface modification and delamination.
[0073] S3: Preparation of Ti3C2T x Mxene reinforced PMMA composites
[0074] S3.1: Surface modified and delaminated Ti3C2T x The solution was centrifuged at 3000 rpm for 5 min to remove the Ti3AlC2 that was not completely etched and the unreacted Ti3C2T x The upper layer solution contains single layer and few layer Ti3C2T x colloidal solution; single-layer and few-layer Ti3C2T x The colloidal solution was vacuum filtered to remove the unreacted KH-570 and obtain surface-modified single-layer and few-layer Ti3C2T x ;
[0075] S3.2: The surface modified single layer and few layer Ti3C2T x After adding to MMA and stirring evenly, the mixture was subjected to ultrasonic layering treatment for 2 h under the protection of argon atmosphere. The temperature was kept below 35 °C during the ultrasonic process to obtain Ti3C2T x The uniformly dispersed MMA solution was used to determine the Ti3C2T x concentration;
[0076] S3.3: Preparation of modified Ti3C2T xA 0.5% mass fraction MMA mixed solution was added with azobisisobutyronitrile (AIBN), the mass ratio of AIBN to MMA mixed solution was 0.4 g:100 g, and the mixture was uniformly mixed and then bulk polymerized. The prepolymerized solution was transferred to a sealed container and polymerized in a water bath at 65 °C for 0.8 h, and then polymerized in a water bath at 95 °C for 1 h. After cooling, KH-570 surface-modified Ti3C2T x MXene reinforced PMMA composites.
[0077] Example 3
[0078] This embodiment provides a method of using KH-570 to modify the surface of Ti3C2T x The preparation method of MXene reinforced PMMA composite material comprises the following steps:
[0079] S1: Ti3C2T x Preparation
[0080] S1.1: After mixing Ti, Al and C powders in a molar ratio of 3:1.4:2, a high-purity ternary layered Ti3AlC2 ceramic block material is prepared by a pressureless sintering process at 1400°C, and the prepared Ti3AlC2 ceramic material is drilled by a drilling machine to obtain Ti3AlC2 ceramic powder; the prepared Ti3AlC2 ceramic powder is sieved through a 325-mesh sieve;
[0081] S1.2: Ti3C2Tx ceramic powder was mixed with 40% hydrofluoric acid at a ratio of 1 g:10 mL, a magnetic rotor was added and stirred in an oil bath at 40 °C for 48 h to remove the Al atomic layer in Ti3C2Tx;
[0082] S1.3: Wash the corroded mixture suspension with 100 mL of deionized water and centrifuge, discard the supernatant, and repeat several times until the pH value of the supernatant is greater than or equal to 6;
[0083] S1.4: After the pH value of the supernatant is greater than or equal to 6, continue to wash with 50 mL of deionized water and centrifuge, pour off the supernatant, repeat 8 to 10 times to obtain the final cleaned Ti3C2T x The mixture was pelleted by centrifugation.
[0084] S2: KH-570 vs Ti3C2T x Surface modification and multilayer Ti3C2T x Ultrasound stratification
[0085] S2.1: Add 0.1g KH-570 to 1g ethanol aqueous solution (the mass ratio of ethanol to deionized water is 9g:1g), add acetic acid to adjust the pH value of the solution to 4, and stir magnetically for 2h to completely hydrolyze KH-570;
[0086] S2.2: The cleaned Ti3C2T x The mixture was centrifuged and precipitated, and then added to the hydrolyzed KH-570 solution. x The mass ratio of the mixture to KH-570 was 1 g:0.5 g. After being stirred evenly, the mixture was subjected to ultrasonic layering treatment for 4 h under the protection of argon atmosphere. The temperature was kept below 35 °C during the ultrasonic process. x While peeling off into single layer and few layers, Ti3C2T x The hydroxyl groups on the surface react with the silanol groups produced by the hydrolysis of KH-570 to form chemical bonds, thus achieving the goal of bonding Ti3C2T x Surface modification and delamination.
[0087] S3: Preparation of Ti3C2T x Mxene reinforced PMMA composites
[0088] S3.1: Surface modified and delaminated Ti3C2T x The solution was centrifuged at 2000 rpm for 8 min to remove the Ti3AlC2 that was not completely etched and the unreacted Ti3C2T x The upper solution contains surface-modified single-layer and few-layer Ti3C2T x colloidal solution; single-layer and few-layer Ti3C2T x The colloidal solution was vacuum filtered to remove the unreacted KH-570 and obtain surface-modified single-layer and few-layer Ti3C2T x ;
[0089] S3.2: The surface modified single layer and few layer Ti3C2T x After adding to MMA and stirring evenly, ultrasonic layering was performed for 2 h under argon atmosphere protection. The temperature was kept below 35 °C during the ultrasonic process to obtain Ti3C2T x The uniformly dispersed MMA solution was used to determine the Ti3C2T x concentration;
[0090] S3.3: Preparation of modified Ti3C2T xAzobisisobutyronitrile (AIBN) was added to the mixed solution of MMA with a mass fraction of 1%, and the mass ratio of AIBN to MMA mixed solution was 0.8g:100g. After mixing evenly, bulk polymerization was carried out, and prepolymerization was carried out in a water bath at 60°C for 1h. The prepolymerized solution was then transferred to a sealed container and polymerized in a water bath at 70°C for 24h, and then polymerized in a water bath at 90°C for 1.5h. After cooling, KH-570 surface-modified Ti3C2T x MXene reinforced PMMA composites.
[0091] Figure 5 KH-570 surface-modified Ti3C2T prepared by the method described in the embodiment of the present invention x Photos of MXene-reinforced PMMA composite samples; (a) is dumbbell-shaped sample 1, used for mechanical properties testing; (b) is rectangular sample 2, used for fracture toughness performance testing.
[0092] Figure 6 (a) and (c) are Ti3C2T prepared by the method of Example 3. x (a) (b) and (d) are CT three-dimensional reconstructed images of composite materials with mass fractions of 0.2% and 1%, respectively. The distribution of MXene in the matrix is drawn based on the test results of (a) and (c), respectively. It can be seen from the figures that MXene in both composite materials is relatively evenly dispersed in the matrix.
[0093] Figure 7 Ti3C2T prepared by the method of Example 3 x The mechanical properties of the composite materials with mass fractions of 0%, 0.1%, 0.2%, 0.5% and 1% are compared after tensile strength test. It can be seen from the figure that when Ti3C2T x When the content is appropriate, the mechanical properties of the composite material will be effectively enhanced.
[0094] Figure 8 Ti3C2T prepared by the method of Example 3 x The mass fractions of Ti3C2T are 0%, 0.1%, 0.2%, 0.5% and 1% respectively. x The mass fraction of 0% is pure PMMA comparison sample, and the fracture toughness and critical energy release rate values are compared; it can be seen from the figure that Ti3C2T x The addition of significantly improves the fracture toughness and critical energy release rate of the composite material.
[0095] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Without departing from the scope and technical principles of the described embodiments, many modifications and changes are obvious to those of ordinary skill in the art, and these modifications and changes should also be regarded as the scope of protection of the present invention.
Claims
1. A modified Ti3C2T x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: include: Ti3C2T x After acid corrosion, the ceramic powder was cleaned and centrifuged to obtain Ti3C2T x The mixture was precipitated by centrifugation; Dissolving KH-570 in an ethanol aqueous solution to prepare a KH-570 solution; The Ti3C2T x The centrifugal precipitation mixture was added to the KH-570 solution, stirred evenly, and then subjected to ultrasonic layering treatment to achieve the Ti3C2T x Surface modification and delamination; Surface modified Ti3C2T x After the solution was centrifuged, the upper layer of the solution was vacuum filtered to obtain surface-modified single-layer and few-layer Ti3C2T x ; The surface modified single layer and few layer Ti3C2T x Add it into methyl methacrylate, stir it evenly and then perform ultrasonic layering treatment to obtain surface modified Ti3C2T x Methyl methacrylate dispersion; Surface modified Ti3C2T x Azobisisobutyronitrile is added to the methyl methacrylate dispersion, the mixture is evenly mixed and then bulk polymerization is carried out to obtain the product.
2. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The Ti3C2T x The method for preparing ceramic powder includes: Ti, Al and C powders are sintered to form a Ti3AlC2 ceramic bulk material, and the prepared ceramic bulk material is ground to obtain Ti3AlC2 ceramic powder; wherein the molar ratio of Ti, Al and C powders is (2.9~3.2):(1~1.4):(1.8~2.2).
3. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The acid corrosion includes: The Ti3AlC2 ceramic powder is placed in a mixed solution of hydrochloric acid and lithium fluoride or an aqueous solution of hydrofluoric acid, and fully stirred at 20-70° C. to obtain a mixed suspension after corrosion.
4. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The preparation method of the KH-570 solution comprises: KH-570 is added to an ethanol aqueous solution, wherein the mass ratio of KH-570 to the ethanol aqueous solution is 1:(10-100), and the mass ratio of ethanol to deionized water in the ethanol aqueous solution is (8-10):(2-0), acetic acid is added to adjust the pH value of the solution to 4-6, and magnetic stirring is performed for 2-4 hours to completely hydrolyze KH-570 to obtain the product.
5. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The Ti3C2T x The mass ratio of the centrifugal precipitation mixture to KH-570 is 1:(0.5~1).
6. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The ultrasonic layering process comprises: The ultrasonic layering treatment was carried out under the protection of argon atmosphere for 1 to 4 hours, and the temperature was kept below 35°C during the ultrasonic process.
7. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The surface modified Ti3C2T x The conditions for centrifugation of the solution include: low-speed centrifugation at 2000-4000 rpm for 2-8 minutes.
8. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The modified Ti3C2T x Ti3C2T in MXene-reinforced polymethyl methacrylate composites x The content of Mxene is 0.001wt.% ~ 20wt.%.
9. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The azobisisobutyronitrile and surface modified Ti3C2T x The mass ratio of methyl methacrylate dispersion is (0.4~0.8):
100.
10. The modified Ti3C2T according to claim 1 x A method for preparing a MXene-reinforced polymethyl methacrylate composite material, characterized in that: The bulk polymerization comprises: Prepolymerize in a water bath at 60-70°C for 0.5-1h to obtain a prepolymer solution; The obtained prepolymer solution was transferred to a sealed container and polymerized in a water bath at 70-90°C for 12-24 hours, and then polymerized in a water bath at 90-95°C for 1-2 hours.